A paradigm shift of integrative learning sytles in training and education. - Osman, Intan
The paper focuses on Integrative Learning System (ILS) and philosophy with an intention to highlight the bases of this paradigm shift. It is hoped that an understanding of the system through examples of its employment in schools and other public and private sectors will be gained. The use of ILS is widespread and throughout the world, however, my main modelling thrusts are Malaysian-based.